2014
DOI: 10.5194/hess-18-1027-2014
|View full text |Cite
|
Sign up to set email alerts
|

Socio-hydrologic drivers of the pendulum swing between agricultural development and environmental health: a case study from Murrumbidgee River basin, Australia

Abstract: Abstract. This paper presents a case study centred on the Murrumbidgee River basin in eastern Australia. It illustrates the dynamics of the balance between water extraction and use for food production, and efforts to mitigate and reverse consequent degradation of the riparian environment. In particular, the paper traces the history of a pendulum swing between an exclusive focus on agricultural development and food production in the initial stages and its attendant socioeconomic benefits, followed by the gradua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
189
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(197 citation statements)
references
References 17 publications
8
189
0
Order By: Relevance
“…Recent literature has begun to validate the core hypothesis through case studies of individual regions [e.g., Kandasamy et al, 2014;Liu et al, 2014]. A synthesis of many case studies showed that four dominant water patterns existed in regions of water crisis [Srinivasan et al, 2012], which leads credence to the premise that common dynamics may emerge across different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has begun to validate the core hypothesis through case studies of individual regions [e.g., Kandasamy et al, 2014;Liu et al, 2014]. A synthesis of many case studies showed that four dominant water patterns existed in regions of water crisis [Srinivasan et al, 2012], which leads credence to the premise that common dynamics may emerge across different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies explored two-way coupling in specific regions: in Chennai, India (Srinivasan, 2015); Portland, Oregon, in the US (Chang et al, 2014); the Murrumbidgee in eastern Australia (Elshafei et al, 2014;Kandasamy et al, 2014;van Emmerik et al, 2014); the Toolibin catchment in western Australia (Elshafei et al, 2014); and Saskatchewan in Canada (Gober and Wheater, 2014). In the majority of these studies, the focus was on water scarcity generated primarily by human water demands.…”
Section: Two-directional Couplingmentioning
confidence: 99%
“…In fact, hydrologic flows in these systems could not be predicted without understanding how preferences have changed. Kandasamy et al (2014) analyze the dynamics of the Murrumbidgee over a 100-year time period. They find that social values and norms have shifted in favor of preserving the environment.…”
Section: Values As Model Feedbacksmentioning
confidence: 99%
“…Through adaption processes, humans co-evolve with the hydrological system, resulting in a pendulum swing from equilibrium in the human-water system (Kandasamy et al, 2014;Sivapalan, 2015). Kandasamy et al (2014) first characterized the concept of the pendulum swing by tracing the 100-year history of the competition for water between agricultural development and environmental health in the Murrumbidgee River basin.…”
Section: Introductionmentioning
confidence: 99%
“…Kandasamy et al (2014) first characterized the concept of the pendulum swing by tracing the 100-year history of the competition for water between agricultural development and environmental health in the Murrumbidgee River basin. Similar dynamics were also found in the humanwater system in the arid Tarim River basin (Liu et al, 2014) and in human-flood interactions (Baldassarre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%